OTIMIZAÇÃO E VALIDAÇÃO DE METODOLOGIA ANALÍTICA PARA A DETERMINAÇÃO DE CHUMBO EM LEITE E RAÇÃO BOVINA UTILIZANDO ESPECTROMETRIA DE ABSORÇÃO ATÔMICA EM FORNO DE GRAFITE - Oliveira, Tatiane Milão de (2015)
Milk is considered an important human food, because contains proteins and essential minerals to develop and sustain human life. Due to the high consumption of milk, contamination by toxic metals must be closely monitored. These contaminants are all harmful to human health, because are cumulative and not have essential activity in the human body. Lead (Pb) is a toxic element that causes biochemical changes and deleterious health effects in humans, even at low concentrations. In addition to analyzing milk samples for determination of lead, it is necessary to monitor the food of milk producing animals (pasture and feed), that can be the source of contamination. In the present study, was performed the optimization and validation of an analytical methodology for determination of Pb in samples of in natura milk and cattle feed using graphite furnace atomic absorption spectrometry (GF AAS). The heating program of graphite furnace was optimized for the two matrices. Optimal pyrolysis and atomization temperatures were, respectively, 500 °C and 1700 °C for the milk matrix and 500 °C and 1900 °C for the cattle feed. The study was evaluated by analytical validation parameters of linearity, detection and quantitation limits, accuracy and precision. Analytical curves in aqueous medium (external standard) were used for determination of Pb in the milk and feed samples. The quantification limits found were low; values of 2.14 mg/L in samples of in natura milk and 5.00 mg/L in samples of cattle feed. The relative standard deviations were less than 10% of the repeatability tests and intermediate precision for both samples. Recoveries in accuracy tests were appropriate for the studied concentration range, from 94.2% to 106.4% for milk samples and from 85.0% to 98.2% for feed samples. After validation of the analytical procedures, raw milk samples were collected from producers in Guarapuava-PR region and Pb concentrations were below 20 mg/L, the maximum quantity of Pb allowed by Brazilian legislation for bovine milk (ANVISA, 2013).